Safety and effectiveness of anticoagulation with non-vitamin K antagonist oral anticoagulants and warfarin in patients on tuberculosis treatment - Hyun-Jung Lee; Hyung-Kwan Kim; Bong-Seong Kim; Kyung-Do Han; Chan Soon Park; Tae-Min Rhee; Jun-Bean Park; Heesun Lee; Yong-Jin Kim (Scientific Reports, 2023)
Abstract Anti-tuberculosis treatment can cause significant drug-drug interaction and interfere with effective anticoagulation. However, there is a lack of evidence and conflicting data on the optimal oral anticoagulation in patients treated for tuberculosis. We investigated the safety and effectiveness of anticoagulation with non-vitamin K antagonist oral anticoagulants (NOACs) and warfarin in patients on anti-tuberculosis treatment. Patients on concomitant oral anticoagulation and anti-tuberculosis treatment including rifampin were identified from the Korean nationwide healthcare database. Subjects were censored at discontinuation of either anticoagulation or rifampin. The outcomes of interest were major bleeding, death, and ischemic stroke. A total 2090 patients (1153 on warfarin, 937 on NOAC) were included. NOAC users, compared to warfarin users, were older, had a lower prevalence of hypertension, heart failure, ischemic stroke, and aspirin use and a higher prevalence of cancer, with no significant differences in CHA2DS2-VASc or HAS-BLED scores. There were 18 major bleeding events, 106 deaths, and 50 stroke events during a mean follow-up of 2.9 months. After multivariable adjustment, the use of NOAC was associated with a lower risk of incident ischemic stroke (HR 0.51, 95% CI 0.27–0.94), while there was no significant difference in risk for major bleeding or death compared with warfarin. These results suggest that NOACs have better effectiveness for stroke prevention and similar safety compared with warfarin in patients on concomitant anti-tuberculosis treatment. This is the first study assessing the safety and effectiveness of NOACs compared to warfarin in this clinical scenario.